Eco-Friendly Composites—Environmental Assessment of Mine Tailings-Based Geopolymers - Kinga Korniejenko; Beata Figiela; Michał Łach; Barbara Kozub (Materials Proceedings, 2024)
Resource efficiency is one of the basic principles of a circular economy (CE). It can be achieved by finding replacements for natural raw materials using anthropogenic raw materials, including by-products from industrial processes and waste materials. In the case of the Polish economy, one possible source is the mining tailings from hard coal exploration and also the waste material from post-mining heaps. The main objective of this work is to present the results of an environmental analysis of geopolymers based on mine tailings. Two geopolymer materials were compared using life cycle assessment (LCA) methodology principles. One of them was based on metakaolin, and the second on industrial waste, mainly from coal shale, as a waste product of hard coal mining. The results show that replacing the original material with alternatives such as metakaolin from mine tailings, reduces the environmental impact, including CO2 emissions. The main findings can be helpful in the implementation of CE, especially the development of sustainable materials, which is one of the crucial elements of introducing closed loops into practice.